The effect of mowing date on some growth characteristics, productivity, and biochemical content of green fodder for several varieties of fodder corn (Zea mays L). (Latakia University Journal -Biological Sciences Series, 2024)
The experiment was carried out at the Pine Research Station of the General Authority for Scientific Agricultural Research in Latakia Governorate, which is about 15 m above sea level, during the 2023 agricultural season, by planting three varieties of forage yellow corn (Ghouta 82, Super Bora, Jameson) in experimental plots and mowing Plants at three main times: T1: about 15 days before the male inflorescence is expelled, T2: during the flowering stage, T3: about 25 days after flowering, according to a randomized complete block design (RCBD) with three replicates. The research aimed to study the effect of mowing date on some growth characteristics, productivity, and biochemical content of green fodder for several varieties of forage yellow corn. Plant height (cm) and a number of morphological indicators (leaf area index (LAI) and total chlorophyll content (µg/g wet weight)), productivity (shoot weight (kg/plant)), quality (protein content (%), and of total soluble sugars (%). The results showed a noticeable increase in plant height (cm), leaf area index (LAI), and shoot total (kg/plant) as the maturity stages of the crop progressed. The percentage of increase, respectively, for the three varieties between the first and third mowing was (126, 136, 122%). For plant height, (82, 78, 70%) for leaf area index, and (71.5, 105.33, 50.21%) for shoot weight, while the percentage of protein decreased between the second and third cuttings and the percentage of decrease reached, respectively, (29.7, 26.08, 11.98). %). The research concluded that the two cultivars (Super Bora and Jameson) were superior to the Ghouta 82 cultivar in most of the studied characteristics and characteristics at the three mowing dates.